Speech delay in toddlers: Are they only `late talkers`? - Zengin-Akkuş, Pınar; Çelen-Yoldaş, Tuba; Kurtipek, Gökçe; Özmert, Elif Nursel (The Turkish Journal of Pediatrics, 2018)
Speech delay is prevalent in toddlers. Although some children with speech delay are able to catch up with their peers with time, the delay might be part of a broader condition such as global developmental delay, which requires specific diagnostic work-up. The current study aimed to present the demographic features, developmental profiles of the first 100 preschool-aged children who were seen at Hacettepe University İhsan Doğramacı Children`s Hospital-Developmental Pediatrics Unit with parental concern of speech delay. Moreover, risk factors associated with speech delay, possible diagnosis and intervention strategies are documented. Thirty-one of 100 children were diagnosed with autism spectrum disorder (ASD) and global developmental delay (GDD). The current study presented that 4 out of 5 toddlers exceeded the recommended TV watching time. Moreover, almost one third of children had a poor linguistic home environment. Three parents whose children were diagnosed with ASD or GDD, refused to be reported as `autism spectrum disorder` or `intellectual disability` with the anxiety of labeling their child. As a result, these children were unable to receive special education paid for by the government. This study presented 31 of 100 children needed further diagnostic work up and early intervention. Therefore, pediatricians should not underestimate speech delay. On the other hand, due to the fact that, the regulations to receive special education and therapy often create anxiety for the parents, we think that this system needs to be updated and special education support should be determined by the special needs of each child.
Keywords: early intervention; linguistic home environment; screen time; special education; speech delay